The factors influencing the tourism development in genting highland - Nurul Awanis Uweishah Mat Noor; Nurul Athirah Azman; Nurul Ayu Wahidah Hanifah; Nurul Arisya Mohamad Ali (2022)
The purpose of this research is to examine the relationship of facilities, safety and security, and services to the development of tourism in Genting Highland. The main objective of this research is to investigate the factors that affect the development of tourists in Genting Highland. It has been found that culture is the main factor influencing travel intention among youth in Penang. Quantitative studies involving the factors of convenience, safety, and security as well as hospitality will be used in our research. We will also use the questionnaire to get answers from respondents regarding the factors listed in the question. The data collected was analysed using the Statistical Package for Social Science (SPSS) version 26.0. SPSS Statistical handles the entire statistical analysis process, such as planning, data collection, analysis, and reporting, to help make better decisions and improve performance. Through this, the study can achieve the objective of the researcher regarding the development of tourism in Genting Highland. Keyword: Genting Highland, tourism development, facility, service, safety and security